Healthcare Professionals' Understandings of the Definition and Determination of Death: A Scoping Review. Issue 4 (25th March 2022) - Zheng, Katina; Sutherland, Stephanie; Hornby, Laura; Wilson, Lindsay; Shemie, Sam D.; Sarti, Aimee J.
Abstract : Background: During the 1950s, advances in critical care, and organ transplantation altered the relationship between organ failure and death. There has since been a shift away from traditional cardiocirculatory based to brain-based criteria of death, with resulting academic controversy, despite the practice being largely accepted worldwide. Our objective is to develop a comprehensive description of the current understandings of healthcare professionals regarding the meaning, definition, and determination of death. Methods: Online databases were used to identify papers published from 2003 to 2020. Additional sources were searched for conference proceedings and theses. Two reviewers screened papers using predefined inclusion and exclusion criteria. Complementary searches and review of reference lists complemented the final study selection. A data extraction instrument was developed to iteratively chart the results of the review. A qualitative approach was conducted to thematically analyze the data. Results: Seven thousand four hundred twenty-eight references were identified. In total, 75 papers met the inclusion criteria. Fourteen additional papers were added from complementary searches. Most were narratives (35%), quantitative investigations (21%), and reviews (18%). Identified themes included: (1) the historical evolution of brain death (BD), (2) persistent controversies about BD and death determination, (3) wide variability in healthcare professionals' knowledge and attitudes, (4) critical need for BD determination revision. Conclusions: We concluded that although BD is widely accepted, there exists variation in healthcare providers' understanding of its conceptual basis. Death determination remains a divisive issue among scholars. This review identified a need for increased opportunities for formal training on BD among healthcare providers.